2022
DOI: 10.3390/v14020195
|View full text |Cite
|
Sign up to set email alerts
|

Mycelia-Assisted Isolation of Non-Host Bacteria Able to Co-Transport Phages

Abstract: Recent studies have demonstrated that phages can be co-transported with motile non-host bacteria, thereby enabling their invasion of biofilms and control of biofilm composition. Here, we developed a novel approach to isolate non-host bacteria able to co-transport phages from soil. It is based on the capability of phage-carrying non-host bacteria to move along mycelia out of soil and form colonies in plaques of their co-transported phages. The approach was tested using two model phages of differing surface hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 88 publications
0
2
0
Order By: Relevance
“…Neutral or negative interactions are often unspecific and transitional. Selected soil bacteria use fungal hyphae as transport routes 4 6 , thus affecting fungal physiology 7 . Multiple interactions occur contemporaneously under natural conditions: a fungus can establish mutualistic interactions with one partner, but develop antagonistic ones with other soil organisms 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Neutral or negative interactions are often unspecific and transitional. Selected soil bacteria use fungal hyphae as transport routes 4 6 , thus affecting fungal physiology 7 . Multiple interactions occur contemporaneously under natural conditions: a fungus can establish mutualistic interactions with one partner, but develop antagonistic ones with other soil organisms 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Motile organisms, including moving patches of bacteria, growing fungi and nematodes, have all been proposed as mechanisms of phage transfer (Dennehy et al, 2006;Ping et al, 2020;You et al, 2022bYou et al, , 2022a, but these previous studies have not demonstrated their operation in spatially structured soil or compost environments. Nevertheless, this growing body of evidence supports recent interest in vectoring interactions as drivers of soil function (Muok and Briegel, 2021).…”
Section: Ecological Interactions In Phage Transfer By Nematodesmentioning
confidence: 99%
“…Pioneering evidence shows that microbes, including phages, may travel by attachment to motile organisms, referred to as hitchhiking. Non-host bacteria travelling along fungal hyphae can cotransport phages even across air-filled voids (You et al, 2022b(You et al, , 2022a. Nematodes, commonly referred to as roundworms, have been found to transport bacteria (Thutupalli et al, 2017) and phages in pure culture (Dennehy et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Phages also are capable of hitching rides on non-bacterial organisms, e.g., such as invertebrates [ 46 , 47 ]. Possible as well is phage movement facilitated by reversible attachment to motile but non-host bacteria [ 48 ], including with those non-host bacteria then moving along fungal mycelia [ 49 , 50 ].…”
Section: Non-diffusive Movementmentioning
confidence: 99%